Pengembangan Model Pembelajaran Bahasa Arab Berbasis AI untuk Meningkatkan Kompetensi Pembelajaran Gramatikal, Tarjamah, dan Maharah di Universitas Nahdlatul Ulama Sunan Giri Bojonegoro - Indriana, Nilna; Ahmad, Mas Tajuddin (AS-SABIQUN, 2025)
Arabic language learning in Islamic higher education faces significant challenges, particularly in mastering grammatical aspects, translation, and skills. The complexity of the Arabic language often becomes a barrier for students. This study aims to develop an Artificial Intelligence (AI)-based learning model to improve Arabic language competence among students at the Nahdlatul Ulama Sunan Giri University of Bojonegoro. Using the ADDIE development model, this research includes the stages of analysis, design, development, implementation, and evaluation. The findings indicate that the integration of AI significantly enhanced students' competencies in grammatical aspects (from 65% to 85%), translation (from 60% to 78%), speaking skills (from 62% to 80%), and text analysis with big data corpus (from 65% to 82%). AI technology enables faster, more adaptive, and interactive learning, offering instant feedback, conversation simulations, and in-depth text analysis. The study concludes that AI can address the challenges in Arabic language learning at Islamic higher education institutions, providing an innovative model that is relevant to global needs. The implication is that the development of similar technology can be adopted by various educational institutions to improve the quality of Arabic language learning nationwide.